Ara h 2: crystal structure and IgE binding distinguish two sub-populations of peanut allergic patients by epitope diversity - Mueller, Geoffrey A. (2011)
BACKGROUND: Peanut allergy affects 1% of the population and causes the most fatal food-related anaphylactic reactions. The protein Ara h 2 is the most potent peanut allergen recognized by 80–90% of peanut allergic patients. METHODS: The crystal structure of the major peanut allergen Ara h 2 was determined for the first time at 2.7 Å resolution using a customized MBP-fusion system. IgE antibody binding to the MBP fusion construct versus the natural allergen was compared by ELISA using sera from peanut allergic patients. RESULTS: The structure of Ara h 2 is a five helix bundle held together by four disulfide bonds and related to the prolamin protein superfamily. The fold is most similar to other amylase and trypsin inhibitors. The MBP-Ara h 2 fusion construct was positively recognized by IgE from 76% of allergic patients (25/33). Two populations of patients could be identified. Sub-population 1 (n=14) showed an excellent correlation of IgE antibody binding to natural versus recombinant Ara h 2. Sub-population 2 (n=15) showed significantly reduced IgE binding to the MBP fusion protein. Interestingly, about 20% of the IgE binding in sub-population 2 could be recovered by increasing the distance between MBP and Ara h 2 in a second construct. DISCUSSION: The reduced IgE binding to the MBP-Ara h 2 of sub-population 2 indicates that the MBP molecule protects an immunodominant epitope region near the first helix of Ara h 2. Residues involved in the epitope(s) are suggested by the crystal structure. The MBP-Ara h 2 fusion constructs will be useful to further elucidate the relevance of certain epitopes to peanut allergy.